Trichodina heterodentata (Ciliophora: Trichodinidae): a new parasite for Piaractus mesopotamicus (Pisces: Characidae) - De Padua, Santiago Benites [UNESP]; Martins, Mauricio Laterca; Carraschi, Silvia Patricia; da Cruz, Claudinei; Ishikawa, Marcia Mayumi (Magnolia Press, 2012)
Trichodinids are mobile peritrichous ciliated protozoa, and widely known as ectocommensals and/or parasites of fish and other aquatic organisms. Little is known about the trichodinid fauna in Brazilian fish. This study reports Trichodina heterodentata Duncan, 1977 as a new parasite for freshwater fish Piaractus mesopotamicus Holmberg, 1887. This is the first record of this trichodinid in southeastern Brazil. Fifty specimens impregnated with 2% silver nitrate and another fifty stained with Giemsa were used for morphometry on the taxonomic characteristics. T. heterodentata in this study is medium size, with a disc-shaped body measuring 49.0 to 61.0 mu m, parasitizing the skin, fins and gills of pacu. Measurement comparisons between the present material and other records from different countries are presented.
Keywords: Trichodinids; fish ectoparasite; aquaculture health